Consumption of a Variety of Vegetables to Meet Dietary Guidelines for Americans' Recommendations Does Not Induce Sensitization of Vegetable Reinforcement Among Adults with Overweight and Obesity: A Randomized Controlled Trial. Issue 6 (23rd March 2021) - Casperson, Shanon L; Jahns, Lisa; Temple, Jennifer L; Appleton, Katherine M; Duke, Sara E; Roemmich, James N
ABSTRACT: Background: Food reinforcement, or the motivation to obtain food, can predict choice and consumption. Vegetable consumption is well below recommended amounts for adults, so understanding how to increase vegetable reinforcement could provide valuable insight into how to increase consumption. Objectives: We sought to determine whether daily consumption of the Dietary Guidelines for Americans (DGA) recommendations for vegetable intake induces sensitization of vegetable reinforcement in adults with overweight and obesity. Methods: Healthy adults with a BMI ≥ 25 kg/m 2 who consumed ≤1 cup-equivalent of vegetables/day were randomly assigned to a vegetable intervention (VI; n = 55) or an attention control (AC; n = 55) group. The VI consisted of the daily provision of vegetables in the amounts and types recommended by the DGA (∼270 g/day) for 8 weeks. Participants were followed for an additional 8 weeks to assess sustained consumption. Compliance was measured weekly by resonance Raman light-scattering spectroscopy (RRS). Vegetable reinforcement was tested at weeks 0, 8, 12, and 16 using a computer choice paradigm. Results: In the VI group, RRS intensity increased from week 0 to 8 (from 22, 990 to 37, 220), returning to baseline by week 16 (27, 300). No change was observed in the AC group. There was no main effect of treatment ( P = 0.974) or time ( P = 0.14) and no treatment x time interaction ( P = 0.44) on vegetable reinforcement. There was no moderating effect of sex ( P = 0.07), age ( P = 0.60), BMI ( P = 0.46), delay discounting ( P = 0.24), 6-n-propylthiouracil taster status ( P = 0.15), or dietary disinhibition ( P = 0.82) on the change in vegetable reinforcement. Conclusions: These findings suggest no effects of the provision of a variety of vegetables to meet DGA recommendations for 8 weeks on vegetable reinforcement and highlight the difficulty in increasing vegetable consumption in adults. This trial was registered at clinicaltrials.gov as NCT02585102.